Using Augmented Reality Media in Three-Dimensional Geometric Shape Material. Issue 1 (May 2021) - Mulbar, U; Alimuddin; Rahmadani; Adhar
Abstract: This research was a development research with a mix method approach. This study aimed to develop augmented reality learning media that was used to help students visualize three-dimensional mathematical objects. It important research because could replace the use of teaching tools that were limited in number, so they could assist teachers in learning process. This research was based on the Plomp model so that it consists of four phases as the following: (1) Preliminary assessment; (2) Designing; (3) Realization; and (4) Tests, Evaluations, and Revisions. The purpose of this study was to examine the validity, implementation, and effectiveness of augmented reality media. The results of this study revealed that augmented reality media was valid to use based on the results of expert validation, practical to use based on the observation sheet of teacher learning and response implementation, and effective to use based on learning outcome tests and student response questionnaires.